Efficacy and safety of amphotericin B deoxycholate versus N-methylglucamine antimoniate in pediatric visceral leishmaniasis : an open-label, randomized, and controlled pilot trial in Brazil - Borges, Myrlena Mescouto (2017)
Introduction: despite their high toxicity, antimonials and amphotericin B deoxycholate are commonly used for treating visceral leishmaniasis (VL). Few studies showing conflictive data about their efficacy and adverse events in pediatric population are available. This study aimed to evaluate efficacy and safety of amphotericin B deoxycholate vs. that of N-methylglucamine antimoniate in treating pediatric VL in Brazil. Methods: this was a randomized, open-label, 2-arm and controlled pilot clinical trial. Treatment naïve children and adolescents with VL without signs of severe illness were treated with N-methylglucamine antimoniate (20mg/kg/day for 20 days) or amphotericin B deoxycholate (1 mg/kg/day for 14 days). All patients were diagnosed with positive direct examination and/or positive PCR for Leishmania spp. performed in bone marrow samples. The primary efficacy end-point was VL cure determined after 180 days of completion of treatment. The analysis was performed using intention-to-treat (ITT) and per protocol (PP) analyses. Results: in total, 101 volunteers were assessed. Efficacy was similar for both groups. The antimonial (n=51) and amphotericin B groups (n=50) had a cure rate of 94.1% and 100%, and 94% and 97.9% according to ITT and PP analyses, respectively. All patients reported adverse events (AE). Serious AE incidence was similar in both groups. Five individuals were excluded from the study because of severe adverse events. Conclusions: N-methylglucamine antimoniate and amphotericin B deoxycholate have similar efficacy and adverse events rate in pediatric patients with VL.